Shedding light on top partner at the LHC - Haider Alhazmi; Jeong Han Kim; Kyoungchul Kong; Ian M. Lewis (Journal of High Energy Physics, 2019)
Abstract We investigate the sensitivity of the 14 TeV LHC to pair-produced top partners (T) decaying into the Standard Model top quark (t) plus either a gluon (g) or a photon (γ). The decays T → tg and T → tγ can be dominant when the mixing between the top partner and top quark are negligible. In this case, the conventional decays T → bW , T → tZ, and T → th are highly suppressed and can be neglected. We take a model-independent approach using effective operators for the T -t-g and T -t-γ interactions, considering both spin- 1 2 $$ \frac{1}{2} $$ and spin- 3 2 $$ \frac{3}{2} $$ top partners. We perform a semi-realistic simulation with boosted top quark tagging and an appropriate implementation of a jet-faking-photon rate. Despite a simple dimensional analysis indicating that the branching ratios BR(T → tγ) ≪ BR(T → tg) due to the electric-magnetic coupling being much smaller than the strong force coupling, our study shows that the LHC sensitivity to T T ¯ → t t ¯ γ g $$ T\overline{T}→ t\overline{t}γ g $$ is more significant than the sensitivity to T T ¯ → t t ¯ gg $$ T\overline{T}→ t\overline{t} gg $$ . This is due to much smaller backgrounds attributed to the isolated high-p T photon. We find that with these decay channels and 3 ab−1 of data, the LHC is sensitive to top partner masses m T ≲ 1.4-1.8 TeV for spin- 1 2 $$ \frac{1}{2} $$ and spin- 3 2 $$ \frac{3}{2} $$ top partners, respectively.